Niedyrektywność w doradztwie filozoficznym = Non-directivity in philosophical counseling - Woszczyk, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a discussion of non-directivity in the practice of philosophical counselling. It shows philosophical counselling as a process that is not axiologically neutral and has a potentially corrective effect on the way the counselee thinks and experiences.
Keywords: niedyrektywność; doradztwo filozoficzne; autonomia; racjonalność; samoświadomość; krytycyzm; neutralność; non-directivity; philosophical counseling; autonomy; rationality; self-awareness; criticism; neutrality